Implementing Guiding Questions Combined with Animation Film to Improve Ninth Graders’ Narrative Writing Skill - Siswanjaya Siswanjaya; Ali Saukah; Francisca Maria Ivone (Pascasarjana UM, 2017)
Abstract: This Classroom Action Research was aimed at improving students’ narrative writing ability at SMPN I Terbanggi Besar, Central Lampung. Lampung, Indonesia. The subjects were 34 students of class IXE. The researcher used writing test as the instrument. The findings showed that the strategy could improve ninth graders’ writing narrative ability. It’s highly recommended that the English teacher use guiding questions combined with animation film to improve the students’ narrative writing ability and the future researchers are suggested to conduct further studies related to the implementation of guiding questions combined with animation film with different kinds of texts and students level.Key Words: writing skill, narrative text, guiding questions, animation film Abstract: Penelitian tindakan kelas ini bertujuan meningkatkan kemampuan siswa menulis text narrative di SMPN I Terbanggi Besar, Lampung Tengah, Lampung, Indonesia. Subjek penelitian ini adalah siswa kelas IXE yang berjumlah 34 siswa. Instrumen penelitian ini adalah tes menulis. Hasil penelitian menunjukkan bhw strategi ini dapat meningkatkan kemampuan menulis narrative siswa kelas IX. Peneliti sangat merekomendasikan kepada guru bahasa Inggris untuk menggunakan guiding questions dikombinasikan dengan film animasi untuk meningkatkan kemampuan siswa menulis teks narrative dan peneliti menyarankan kepada peneliti selanjutnya untuk melaksanakan penelitian berhubungan dengan penerapan guiding question dikombinasikan dengan film animasi pada jenis teks dan tingkat siswa yang berbeda.Kata kunci : Kemampuan menulis, teks narrative, pertanyaan penuntun, film animasi